Development of a Rapid and Confirmatory Method to Identify Ganoderic Acids in Ganoderma Mushrooms - Sun, Hao H.; Qi, Ying; Zhao, Lingling (Frontiers in Pharmacology, 2012)
To examine the composition of lanostanoids in Ganoderma lucidum, we have developed a liquid chromatography-mass spectrometry (LC-MS) method by using the ganoderic acids isolated in our laboratory as reference standards. The identity of 14 peaks in the high performance liquid chromatogram of G. lucidum has been confirmed. By using the HPLC retention times of these ganoderic acids and their mass fragmentation patterns established in this paper, one can use LC-MS to analyze G. lucidum without requiring the reference standards of these 14 ganoderic acids. Subsequently, only the HPLC-UV method would be needed to analyze routine samples of G. lucidum.